Analisis Yuridis terhadap Hak dan Kewajiban Karyawan Outsourcing Berdasarkan Undang-undang Ketenagakerjaan (PT. Garda Wibawa Sukses) - Filia Filia; Rivaldo Putra Wijaya (Universitas Medan Area, 2019)
Outsourcing systems are in great demand by other companies because the services of outsourcing companies help other companies run their businesses. Law No. 13 of 2003 has helped many new companies or companies that have been established to make efficiency through the use of outsourcing company services to produce certain products or services. In this research, the company that we research is outsourcing company PT Garda Wibawa Sukses. Employees at this company are given legal protection, such as: economic protection, social protection, and technical protection and this company also provides legal protection for female employees. In addition, employees in this company also have rights and obligations attached to each of them. Rights owned by employees can be obtained in accordance with those owned by employees in general. In addition to having rights, employees must obey the obligations set by the company and have been agreed by both parties. This type of research uses the Normative Juridical method, namely by conducting an analysis of outsourcing companies regarding the rights and obligations obtained by outsourcing employees at PT Garda Wibawa Sukses in accordance with statutory regulations.